The Impact of Economic Policy on E-commerce Growth and Consumer Behavior: Lessons from the COVID-19 Pandemic - Dedy Setiawan (Politeknik Siber Cerdika Internasional, 2025)
The COVID-19 pandemic has rapidly changed the global economic landscape, accelerating the growth of e-commerce and changing consumer behavior. The economic policies implemented by the government to support the economy during this crisis played an important role in encouraging the adoption of digital technology and online shopping. This study aims to analyze the impact of economic policies on e-commerce growth and consumer behavior during the pandemic. The method used is a case study that includes secondary data analysis from government reports, consumer surveys, and e-commerce industry statistics. The results of the study show that policies that support internet access, subsidies for small businesses, and tax incentives significantly increase consumer participation in e-commerce. In addition, the study revealed that consumer behavior has shifted to online shopping preferences, with increasing trust in digital transactions and a more convenient shopping experience. These findings provide important insights for stakeholders and policymakers to formulate better strategies in supporting future e-commerce growth and tailoring economic policies relevant to changing consumer behavior.